2022
DOI: 10.1017/jfm.2022.697
|View full text |Cite
|
Sign up to set email alerts
|

Oblique transition in hypersonic double-wedge flow

Abstract: We utilize resolvent and weakly nonlinear analyses in combination with direct numerical simulations (DNS) to identify mechanisms for oblique transition in a Mach $5$ hypersonic flow over an adiabatic slender double wedge. Even though the laminar separated flow is globally stable, resolvent analysis demonstrates significant amplification of unsteady external disturbances to the linearized flow equations. These disturbances are introduced upstream of the separation zone and they lead … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…(2021 b ) investigated numerically a transitional flow at Mach 5 over a hollow cylinder/flare, and found several possible transition paths, such as second mode, oblique mode and non-modal growth. Oblique transition in a hypersonic double-wedge flow was revealed by Dwivedi, Sidharth & Jovanović (2022).…”
Section: Introductionmentioning
confidence: 95%
“…(2021 b ) investigated numerically a transitional flow at Mach 5 over a hollow cylinder/flare, and found several possible transition paths, such as second mode, oblique mode and non-modal growth. Oblique transition in a hypersonic double-wedge flow was revealed by Dwivedi, Sidharth & Jovanović (2022).…”
Section: Introductionmentioning
confidence: 95%
“…Recent computational investigation of convective and global boundary-layer instabilities over a sharp cone-cylinder-flare model at Mach 6 by Paredes et al (2022) captured the distinct lobes within the disturbance amplification spectra measured with wall-pressure sensors at the BAM6QT with 10 • flare, and reported that the oblique Mack's first-mode waves that begin to amplify over the cone continue to grow along the separated shear layer. Weakly nonlinear input-output analysis and direct numerical simulations by Dwivedi, Sidharth & Jovanovic (2022) for a globally stable double wedge flow at Mach 5 discussed that shear stress fluctuation due to streamline curvature as the physical mechanism for the amplification of the oblique waves.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Dwidedi et al 29 quantified the amplification of streaks due to external harmonic excitation in supersonic laminar boundary layer and hypersonic compression ramp flows. Using the same framework, Dwidedi et al 30 investigated oblique transition in a Mach 5 hypersonic flow over an adiabatic slender double-wedge. For the turbulent regime, Bae et al 31 Although the above findings provide a good understanding of the amplification of first and second modes and streaks in supersonic boundary layers, it should be pointed out that the above mentioned models have some limitations.…”
Section: Introductionmentioning
confidence: 99%